A machine learning approach for the diagnosis of obstructive sleep apnoea using oximetry, demographic and anthropometric data - Zhou Hao Leong; Shaun Ray Han Loh; Leong Chai Leow; Thun How Ong; Song Tar Toh (Singapore Medical Journal)
Introduction: Obstructive sleep apnoea (OSA) is a serious but underdiagnosed condition. Demand for the gold standard diagnostic polysomnogram (PSG) far exceeds its availability. More efficient diagnostic methods are needed, even in tertiary settings. Machine learning (ML) models have strengths in disease prediction and early diagnosis. We explored the use of ML with oximetry, demographic and anthropometric data to diagnose OSA. Methods: A total of 2,996 patients were included for modelling and divided into test and training sets. Seven commonly used supervised learning algorithms were trained with the data. Sensitivity (recall), specificity, positive predictive value (PPV) (precision), negative predictive value, area under the receiver operating characteristic curve (AUC) and F1 measure were reported for each model. Results: In the best performing four-class model (neural network model predicting no, mild, moderate or severe OSA), a prediction of moderate and/or severe disease had a combined PPV of 94%; one out of 335 patients had no OSA and 19 had mild OSA. In the best performing two-class model (logistic regression model predicting no–mild vs. moderate–severe OSA), the PPV for moderate–severe OSA was 92%; two out of 350 patients had no OSA and 26 had mild OSA. Conclusion: Our study showed that the prediction of moderate–severe OSA in a tertiary setting with an ML approach is a viable option to facilitate early identification of OSA. Prospective studies with home-based oximeters and analysis of other oximetry variables are the next steps towards formal implementation.